Psychic symptomatology in the patients admitted to the policlinics other than psychiatry policlinic - Oguzhanoglu, N.K.; Oguzhanoglu, A.; Akyol, A.; Yildiz, M. (My University, 1994)
With the viewpoint that biologic and psychologic parameters interact with each other, we try to search psychologic symptoms accompanying the physical disorders. A hundred outpatient which have been chosen among the patients admitted to the policlinics other than psychiatry policlinic of Firat University Hospital on July-December 1992, were involved in study. SCL-90 R (Symptom Check List) and STAI X (State Traid Anxiety Inventory) were performed on the patients and all were interviewed. Diagnosis have been established on the basis of the criteria in DSM III R (Diagnostic and Statistical Manual III Revised). Same tests were performed on 53 patients as control group which admitted to psychiatry policlinic and diagnosed not to have psychosis during the same period. Sociodemographic properties and diagnosis were evaluated on the basis of the percentage distribution. and the comparison of the tests between two groups on the basis of students test Sociodemographic properties in both groups showed similarity. In study group any psychiatric diagnosis has not been established in 53 % of the patients. Nineteen percent of patients has not met the criteria of axis I but has presented the symptoms of depression and anxiety. We defined psychological factors affecting physical condition in 11 % of patients and anxiety disorder in 7 %. Cluster C personality properties has been defined prominently in both groups. In control group the psychopathologic values of the tests have been revealed to be high as it has been expected and in the study group the Values of somatization, obsessive-compulsive signs and supplementary scale have been revealed to be high.
Keywords: Diagnosis; Nonpsychiatric policlinics; Psychological symptoms